A New Enthalpy of Formation Test Set Designed for Organic Fluorine Containing Compounds (Adv. Theory Simul. 8/2022). Issue 8 (11th August 2022) - Si, Yitao; Liu, Yingzhe; Lai, Weipeng; Ma, Yiding; Shi, Jinwen; Wang, Bozhou; Liu, Maochang; Yu, Tao
Abstract : A New Enthalpy of Formation Test Set for Finding Organic Fluorine Containing Compounds Density functional theory often performs worse predicting gas phase enthalpy of formation for fluorine compounds than it does for other systems. The numerical bias somewhat lacks a systematic quantification; the evaluation of various commonly used computational levels will facilitate research on fluorine chemistry. In article 2200093, Si, Yu and co‐workers propose a new test set for fluorine containing compounds, and quantitatively analyze the differences induced by various computational levels and strategies.